Medical management of bilateral corneal opacity in an Asian elephant (Elephas maximus): A case report - Paul, Pranab; Hasan, Tanjila; Rahman, Md. Mizanur (Journal of Advanced Veterinary and Animal Research, 2018)
Objective: This study was aimed at studying efficacy of medical management of corneal opacity in an Asian elephant (Elephas maximus). Material and methods: A 42 years old male Asian elephant was brought to the Teaching Veterinary Hospital (TVH) at Chittagong Veterinary and Animal Sciences University (CVASU) with a history of chronic lacrimation and impaired vision. On clinical examination, the animal was found apparently healthy. Opthalmological examination tentatively revealed the condition as corneal opacity. The left eye was much more affected as compared to the right one. Medical management was instituted with topical administration of ciprofloxacin, dexamethasone, subconjunctival prednisolone and dexamethasone along with intramuscular ketoprofen (at 1 mg/Kg bwt) and vitamin A (at 5000 IU/Kg bwt). Results: The “mahout” (elepenat caretaker) of the elephant was kept in close contact over cell phone to follow up the progress of the condition. Clinical examination after 19 days revealed complete recovery of the cornel opacity. There was no sign of lacrimation and the animal regained its normal vision. Conclusion: The treatment protocol successfully eliminated the discomfort along with corneal opacity and lacrimation in an Asian elephant. http://doi.org/10.5455/javar.2018.e244